2013
DOI: 10.1517/14728222.2013.828037
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cdc42 in cancer

Abstract: Introduction The Rho GTPases are a family of proteins that control fundamental cellular processes in response to extracellular stimuli and internal programs. Rho GTPases function as molecular switches in which the GTP-bound proteins are active and GDP-bound proteins are inactive. This review will focus on one Rho family member, Cdc42, which is overexpressed in a number of human cancers, and which might provide new therapeutic targets in malignancies. Areas covered In this review the key regulators and effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 97 publications
0
71
0
1
Order By: Relevance
“…By its GAP domain, it inactivates Rho GTPases such as CDC42 (a small GTPase of the Rho family) by hydrolyzing its GTP into GDP (51,52). In its active form (bound to GTP), CDC42 is able to mediate signaling cascades leading to activation of more than 20 downstream effectors involved in proliferation, migration, adhesion, and cytoskeleton remodeling (51); mTOR and p70S6K are among the effectors activated by CDC42 (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…By its GAP domain, it inactivates Rho GTPases such as CDC42 (a small GTPase of the Rho family) by hydrolyzing its GTP into GDP (51,52). In its active form (bound to GTP), CDC42 is able to mediate signaling cascades leading to activation of more than 20 downstream effectors involved in proliferation, migration, adhesion, and cytoskeleton remodeling (51); mTOR and p70S6K are among the effectors activated by CDC42 (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…As such, Cdc42 is a model protein system to characterize molecular details of Ras-related Protein-Protein Interactions [PPIs]. Progress has been made in understanding the pathogenesis of Cdc42-stimulated hyperactivity [5]. However, targeting small molecules towards PPIs involving Cdc42 have remained difficult, mainly because of the challenges in determining the most appropriate binding interfaces on the protein to target [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically targeting Cdc42 for therapeutic purposes has seen some recent progress [12] [13] [14], and a few reviews have highlighted the promise of these new approaches [5] [15]. Cdc42, which is post-translationally modified to target the periphery of the inner cell membrane where it functions, cycles between active GTP-bound and inactive GDP-bound states, and this process is regulated by Cdc42 has a six-stranded ÎČ-sheet, five α-helices, and a guanine nucleotidebinding site with a conserved sequence that recognizes the guanine base, the ÎČ-phosphate and a magnesium ion [16 Targeting these protein-binding surfaces to influence Cdc42 involved PPIs, while still a daunting challenge, remains vital as Cdc42-stimulated hyperactivity has been a hallmark of this protein's involvement in various cancers [23].…”
Section: Introductionmentioning
confidence: 99%
“…In human, miR-137 has been extensively investigated and shown to play important roles in various cancers, cell cycle signaling, and embryonic stem cell development. Studies have demonstrated that miR-137 targets cell division control protein 42 (Cdc42), a Rho GTPase family protein up-regulated in many human cancer types, such as colorectal, lung, and breast cancers (Arias-Romero and Chernoff 2013). Through the inhibition of the Cdc42/PAK signaling pathway, miR-137 decreases the proliferation, invasion, and G0/G1 cell cycle progression of colorectal cancer cells (Liu et al 2011;Zhu et al 2013).…”
mentioning
confidence: 99%